Neuromuscular training to prevent anterior cruciate ligament injury in the female athlete - Fischer, D. V. (Strength and Conditioning Journal, 2006)
Despite the identification of effective anterior cruciate ligament (ACL) injury prevention exercise programs,female athletes remain at a 4- to 6-fold greater risk of ACL injury compared to male athletes. One possible explanation for the lack of improvement in ACL injury risk in female athletes is an inadequate dissemination of information regarding effective intervention strategies. This article presents gender differences in neuromuscular control that may place the female athlete at increased risk for ACL injury and information on the design and implementation of a neuromuscular training program to reduce the risk of ACL injury in female athlete.